Leptomeningeal Metastasis from Malignant Pleural Mesothelioma - Petrovic, Boris D. (AJNR Am J Neuroradiol, 2004)
Summary: Leptomeningeal metastasis from malignant mesothelioma is very rare; to our knowledge, only one imaging report exists in the literature. We present the case of widespread leptomeningeal lesions secondary to a malignant mesothelioma in a 61-year-old woman.